Efficient methodology to produce a duloxetine precursor using whole cells of Rhodotorula rubra. Issue 9 (1st June 2016) - Rimoldi, Isabella; Facchetti, Giorgio; Nava, Donatella; Contente, Martina Letizia; Gandolfi, Raffella
Graphical abstract: Abstract: Different types of yeasts were employed as biocatalysts in the reduction of β-ketonitriles. The red microorganism, Rhodotorula rubra, was selected as the best performing catalyst in the reduction of different substituted ketonitriles giving total stereoselectivity in most cases (90–99% ee). In particular, its use as fresh and lyophilised cells was expanded to a semi-preparative scale for the production of the duloxetine precursor1a . R. rubra was screened in the reduction of alkylation products in comparison with Pichia henricii for assignment of configuration of products2a and11a after derivatisation with S -MPA. Abstract : ( S )-3-Hydroxy-3-(thiophen-2-yl)propanenitrile: C7 H7 NOS Ee = 99% from HPLC [ α ]D 20 = −42.1 ( c 0.8, CHCl3) Source of chirality: Rhodotorula rubra Absolute configuration: ( S )